2020
DOI: 10.1016/s0140-6736(20)31412-4
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for the female academic during the COVID-19 pandemic

Abstract: between girls and boys. We call for a gendered perspective in developing policy responses by tackling the sexual and reproductive health and socioeconomic issues addressed here to bring girls back to school after the measures to contain the COVID-19 pandemic end. We also ask governments to collect data specifically on non-paid housework and childcare respon sibilities frequently ignored when investigating the consequences of child labour. Addressing the health and socioeconomic issues girls might face during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
237
1
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(275 citation statements)
references
References 5 publications
13
237
1
6
Order By: Relevance
“…2 Current public health mandates, such as school and daycare closures and shelter-in-place ordinances, likely exacerbate this imbalance between male and female physicians, impacting clinical activities, grant application submissions, manuscript preparation, and teaching. [19][20][21][22][23][24] In order to minimize potential adverse effects on productivity, advancement, and promotion, we recommend institutional leaders and their operations, human resources, and faculty affairs teams do the following: & Develop social support hubs and practical seminars focused on resiliency, managing vicarious trauma, and building camaraderie and community. Be mindful that these opportunities do not place additional burden on women physicians to organize and execute.…”
Section: ) Compensation and Professional Effort: In The Unitedmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Current public health mandates, such as school and daycare closures and shelter-in-place ordinances, likely exacerbate this imbalance between male and female physicians, impacting clinical activities, grant application submissions, manuscript preparation, and teaching. [19][20][21][22][23][24] In order to minimize potential adverse effects on productivity, advancement, and promotion, we recommend institutional leaders and their operations, human resources, and faculty affairs teams do the following: & Develop social support hubs and practical seminars focused on resiliency, managing vicarious trauma, and building camaraderie and community. Be mindful that these opportunities do not place additional burden on women physicians to organize and execute.…”
Section: ) Compensation and Professional Effort: In The Unitedmentioning
confidence: 99%
“…[26][27][28][29][30][31] In the current pandemic, preliminary communications show a stark decrease in submissions to scientific journals by women investigators 32,33 as well as fewer first-author COVID-19 publications compared with men. [20][21][22][23][24] Additionally, educators have had to accommodate rapid changes in curricula and adapt teaching techniques for remote learning, which may impede or supersede other scholarly and educational endeavors. To combat these barriers to academic productivity, we recommend institutional leaders, including offices of faculty affairs and research, do the following:…”
Section: ) Compensation and Professional Effort: In The Unitedmentioning
confidence: 99%
“…Analysis of 60,000 journals showed a dramatic collapse in women first-authorship in May, 2020, by seven percentage points relative to 2019 (Matthews, 2020). Additionally, studies have found significant gender gaps in authorship on COVID-19 related research (Amano-Patiño, Faraglia, Giannitsarou, & Hasna, 2020;Andersen, Nielsen, Simone, Lewiss, & Jagsi, 2020;Gabster, van Daalen, Dhatt, & Barry, 2020;Pinho-Gomes et al, 2020). Only one analysis of submissions to a single journal found minimal or no gender differences in productivity during the early days of the pandemic (Dolan & Lawless, 2020).…”
Section: Gender Differences In Productivity During the Pandemicmentioning
confidence: 99%
“…These ndings support anecdotal reports that women academics have been underrepresented in newspaper coverage and evidence-based data demonstrating the exclusion of women from academic publication and leadership during the COVID-19 pandemic. [1][2][3][4] The proportion of women experts cited in newspaper articles about the COVID-19 pandemic is greater than previous studies of the representation of women in news media. In a 2008 study of UK newspapers, only 16% of all quoted scientists were female.…”
Section: Discussionmentioning
confidence: 98%
“…Anecdotal reports of the impact of increased barriers for women academics due to COVID-19 1 have been supported by evidence of a decrease in publications for women academics since the pandemic began. 2,3 Further, women are underrepresented in pandemic decision-making and leadership roles. 4 Altogether, this growing evidence highlights that women academics are being excluded from key opportunities during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%